Protective role of Decylubiquinone against secondary melanoma at lung in B16F10 induced mice by reducing E-cadherin expression and ameliorating ROCKII-Limk1/2-Cofiliin mediated metastasis - Chatterjee, Sujan; Patra, Debajyoti; Ghosh, Pujita; Banerjee, Soumi; Mishra, Snehasis; Chakraborty, Pratip; Chowdhury, Kaustav Dutta; Basu, Anupam; Sadhukhan, Gobinda Chandra (Cellular signalling, 2023)
Melanoma is one of the most consequential skin cancer with a rising death incidences. Silent but belligerent nature of metastatic sprouting is the leading cause of melanoma related mortality. Invasion of metastatic cells and re-expression of E-Cadherin play the crucial role in the establishment of secondary tumor at distal sites. Thus, manipulation of tumor cell invasion in parallel to regulation of E-Cadherin expression can be considered as potential anti-metastatic strategy. Evidences suggested key role of reactive oxygen species associated ROCK activities in the modulation of metastatic invasion via F-actin stabilization. Here, we first-time report Decylubiquinone, a dietary Coenzyme Q10 analog, as an effective attenuator of pulmonary metastatic melanoma in C57BL/6 mice. Current study depicted detailed molecular interplay associated with Decylubiquinone mediated phosphorylation of ROCKII at Tyr722 along with reduced phosphorylation of ROCKII Ser1366 leading to suppression of Limk1/2-Cofilin-F-actin stabilization axis that finally restricted B16F10 melanoma cell invasion at metastatic site. Analysis further deciphered the role of HNF4α as its nuclear translocation modulated E-Cadherin expression, the effect of reactive oxygen species dependent ROCKII activity in secondarily colonized B16F10 melanoma cells at lungs. Thus unbosoming of related signal orchestra represented Decylubiquinone as a potential remedial agent against secondary lung melanoma. [Display omitted] •Decylubiquinone (Dub) mitigates B16F10 induced secondary lung melanoma.•Dub calibrates intercellular ROS level and modulates ROCKII activity in melanoma.•Dub mediated deactivation of ROCKII attenuates Limk1/2-Cofilin-Factin stabilization.•Dub censors E-Cadherin re-expression by restricting HNF4α/ID1 nuclear translocation.